Direct use of the solid waste from oxytetracycline fermentation broth to construct Hf-containing catalysts for Meerwein–Ponndorf–Verley reactions. Issue 23 (13th April 2021) - Chen, Yuxin; Yao, Xuefeng; Wang, Xiaolu; Zhang, Xuefeng; Zhou, Huacong; He, Runxia; Liu, Quansheng
Abstract : An efficient Hf-OFR catalyst was designed in which Hf 4+ interacts with oxygen-containing acidic groups in oxytetracycline fermentation broth residues for MPV reactions. Abstract : The oxytetracycline fermentation broth residue (OFR) is an abundant solid waste in the fermentation industry, which is hazardous but tricky to treat. The resource utilization of the waste OFR is still challenging. In this study, a novel route of using OFR was proposed that OFR was used as the organic ligands to construct a new hafnium based catalyst (Hf-OFR) for Meerwein–Ponndorf–Verley (MPV) reactions of biomass-derived platforms. The acidic groups in OFR were used to coordinate with Hf 4+, and the carbon skeleton structures in OFR were used to form the spatial network structures of the Hf-OFR catalyst. The results showed that the synthesized Hf-OFR catalyst could catalyze the MPV reduction of various carbonyl compounds under relatively mild reaction conditions, with high conversions and yields. Besides, the Hf-OFR catalyst could be recycled at least 5 times with excellent stability in activity and structures. The prepared Hf-OFR catalyst possesses the advantages of high efficiency, a simple preparation process, and low cost in ligands. The proposed strategy of constructing catalysts using OFR may provide new routes for both valuable utilization of the OFR solid waste in the fermentation industry and the construction of efficient catalysts for biomass conversion.